Studies on the Introduction of Mochania macrophylla for Cultivation of Lac - Purkayastha, B. K. (Indian Forester, 1969)
The results of investigations are summarised as follows: (1) The optimum time of seed collection is October-November. (2) Seeds have a dormancy period of 5-6 months. (3) Seeds remain viable for a period of three years. Percentage of germination is not affected much and, on the other hand, old seeds germinate in a shorter period. (4) It is advisable to pretreat the seeds either in boiling water or in cold water before sowing. This treatment improves germination percentage and reduces the period of germination. (5) Transplanting with the balls of earth is the most effective method of propagation. Seedlings should be raised in nursery beds in April for transplantation because these develop larger length of shoots for settlement of lac insects.